Pengaruh Kepemimpinan Situasional Kepala Desa Terhadap Motivasi Kerja Aparat Kantor Desa Masing Kecamatan Lilirilau Kabupaten Soppeng - Adrian Maulana; Muh. Hasbi Abbas; Muh. Justiawal Ari (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The background of this study, based on the results of observations that have been conducted, highlights the need for adjustments between leaders and subordinates. The leadership style currently exhibited appears monotonous and requires further adaptation to achieve better synergy. The purpose of this research is to examine the influence of situational leadership applied by the Village Head on the work motivation of staff at the Masing Village Office, Lilirilau District, Soppeng Regency. This study employs a census method, where the data source includes the entire population as the sample, using questionnaires as the primary data collection technique. The sample in this research consists of 17 respondents. Data collection techniques include observation, questionnaires, and documentation. Data analysis techniques employed are descriptive quantitative analysis, correlation analysis, and simple regression analysis. Based on the analysis and discussion conducted, the writer concludes that The situational leadership of the Village Head of Masing falls into the very good category. The work motivation of staff at the Masing Village Office is also categorized as very good. Situational leadership positively influences the improvement of staff work motivation at the Masing Village Office. The findings of this study indicate that there is a positive influence of the Village Head's situational leadership on the work motivation of staff at the Masing Village Office, Lilirilau District, Soppeng Regency.